Monitoring training stress in elite swimmers using biological markers - Van Heest, J. L.; Skinner, J.; Cappaert, J. M.; Rodgers, C. D.; Ratliff, K. (Medicine & Science in Sports & Exercise, 1996)
Elite male swimmers (N = 7) were evaluated with performance and laboratory tests and subjective interviews periodically over nine months. Subjective descriptions of overtraining indicated high levels on three occasions (at least 5 of 7) while no reports were offered at the other times. These reports in no way coincided with the few (LDH and CPK) significant but inconsistent biological differences. A time-lag between subjective reports and some elevated markers was noted. Implication: This paper supports the contention that overtraining, at least initially, is primarily a central nervous system phenomenon. Psychological measures locate this state whereas the often unrelated or insensitive common biological markers do not. If one waits until biological or physiological changes occur, an athlete may be too damaged in a physiological/structural sense to be able to effect a relatively short "cure."